GZ17-6.02 Interacts With [MEK1/2 and B-RAF Inhibitors] to Kill Melanoma Cells - Booth, Laurence; West, Cameron; Von Hoff, Daniel; Kirkwood, John M.; Dent, Paul (Frontiers in Oncology, 2021)
We defined the lethal interaction between the novel therapeutic GZ17-6.02 and the standard of care combination of the MEK1/2 inhibitor trametinib and the B-RAF inhibitor dabrafenib in PDX isolates of cutaneous melanoma expressing a mutant B-RAF V600E protein. GZ17-6.02 interacted with trametinib / dabrafenib in an additive fashion to kill melanoma cells. Regardless of prior vemurafenib resistance, the drugs when combined interacted to prolong ATM S1981 / AMPK T172 and eIF2 alpha S51 phosphorylation and prolong the reduced phosphorylation of JAK2 Y1007, STAT3 Y705 and STAT5 Y694. In vemurafenib-resistant cells GZ17-6.02 caused a prolonged reduction in mTORC1 S2448, mTORC2 S2481 and ULK1 S757 phosphorylation; regardless of vemurafenib resistance, GZ17-6.02 caused a prolonged elevation in CD95 and FAS-L expression. Knock down of eIF2 alpha, Beclin1, ATG5, ATM, AMPK alpha, CD95 or FADD significantly reduced the ability of GZ17-6.02 to kill as a single agent or when combined with the kinase inhibitors. Expression of activated mTOR, activated STAT3, activated MEK1 or activated AKT significantly reduced the ability of GZ17-6.02 to kill as a single agent or when combined with kinase inhibitors; protective effects that were significantly less pronounced in cells treated with trametinib / dabrafenib. Regardless of vemurafenib resistance, the drugs alone or in combination all reduced the expression of PD-L1 and increased the levels of MHCA which was linked to degradation of multiple HDAC proteins. Our findings support the use of GZ17-6.02 in combination with trametinib / dabrafenib in the treatment of melanomas expressing mutant B-RAF V600E proteins.